2020
DOI: 10.1016/j.xfss.2020.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Photoacoustic laser effects in live mouse blastocysts: pilot safety studies of DNA damage from photoacoustic imaging doses

Abstract: Objectives: To investigate the laser safety of photoacoustic imaging. In photoacoustic imaging, a pulsed laser of several nanoseconds is used to illuminate biological tissue, and photoacoustic waves generated by optical absorption are used to form images of the tissue. Photoacoustic imaging is emerging in clinical applications; however, its potential use in reproductive medicine has yet to be reported. Design: Assessment of photoacoustic laser safety before its adoption by clinical reproductive medicine. Setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…Temperature rise and possible thermal damages for photoacoustic imaging have been assessed in several papers. [48][49][50] These studies have consistently found that the heat deposition necessary for photoacoustic imaging is generally safe and does not result in cell deaths. Indeed, photoacoustic imaging has demonstrated that a few mK temperature rise in the sample can produce reasonably strong acoustic signal.…”
mentioning
confidence: 88%
“…Temperature rise and possible thermal damages for photoacoustic imaging have been assessed in several papers. [48][49][50] These studies have consistently found that the heat deposition necessary for photoacoustic imaging is generally safe and does not result in cell deaths. Indeed, photoacoustic imaging has demonstrated that a few mK temperature rise in the sample can produce reasonably strong acoustic signal.…”
mentioning
confidence: 88%
“…DNA damage has been also studied in vivo through photoacoustic imaging of blastocysts exposed to different doses of laser. 12 Recently, an improvement of PAT was developed to generate high-quality images, the technology is named photoacoustic radar tomography (PART). PART incorporates modulated light from diode lasers, and the ultrasonic echo, generated by light-absorbing elements within the tissue, is detected by a transducer array and digitized.…”
Section: Photoacoustic Spectroscopy (Pas)mentioning
confidence: 99%